Marketing Strategy of Foreign Construction Company in Indonesia - Dong, Yan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
construction company in Indonesia. This study using qualitative research with participants of PT Pengembangan Industri Logam to make mini model. Mini-model theory was obtained that displays four (4) latent variables that determine the success of marketing strategy. Mini Model Theory which product quality, product price, word of mouth marketing and government policy. Product price and government policy negatively affects marketing strategy. This study result 4 latent variable from data collection which are product quality, product price, word of mouth marketing and government policy. From the coding process known that product price and government policy give negative effects on marketing strategy.